ANALISIS EFEKTIFITAS DIMENSI KEPEMIMPINAN (Studi Kasus pada RSUD Prof. dr. Soekandar Mojokerto) - Sri Handari W; Sujatmiko Sujatmiko (Universitas Muhammadiyah Yogyakarta, 2013)
Success in the management of District Hospital of Prof. dr. Soekandar Mojokerto closely related to leadership effectiveness at the managerial level. Measurement of the effectiveness of leadership that has been applied by a manager can be judged from the point of view of the perception of employees, so that it can be seen the gap between perception and expectation of the employees. This study aims to perceive and identify the expectations of leadership based on appraisals, as well as analyzing the things that become priorities for improving leadership effectiveness based on gap analysis. Measurement of leadership effectiveness used three dimensions such as; relationship of innate leadership, task structure, position power of the leader. Research is a descriptive survey using a method stratified random sampling. Numbers of samples were 126 employees who occupy positions in hospital management at District Hospital of Prof. dr. Soekandar Mojokerto. The results showed that the assessment of employees on the effectiveness of leadership in District Hospital of Prof. dr. Soekandar Mojokerto had been viewed that it did not in line with expectations at both the head of departement, head of section, coordinators and staff space. While the results of the gap analysis showed that there was a lack of appreciation of the employees,because of less rewarding high to performing employees, achieving promotion to employees and find it was fairless in giving punishment to the employees. To improve the effectiveness of leadership in District Hospital of Prof. dr. Soekandar Mojokerto need step of improvement priorities such as the development of a vision and mission hospitals, tariffs improvement, strengthen partnerships, develop human resources and public services.